Three-Layers Slab Waveguide with Chiral Metamaterial Core and Graphene Interfaces - Hameed, Hawraa; A. Yasser, Hassan (University of Thi-Qar Journal of Science, 2024)
We investigate the dispersion relation of guided waves in a three-layered slab waveguide, with one layer filled with chiral metamaterial and the other two filled with normal materials. This waveguide model contains an interface between adjacent layers. Graphene was used for this purpose due to its excellent optical properties. The interface thickness is , where three monolayer graphene was used. Propagation equations and special cases for this type of structure and graphene properties were obtained. Such phenomena have also been given physical explanations. Our theoretical work has been validated by simulation findings. These chiral structures have potential uses in millimeter-wave and microwave-integrated circuits.